INDONESIAN PEOPLE RISK FACTORS OF NOCTURIA (TWO OR MORE VOIDS PER NIGHT) OLDER THAN 40 YEARS-OLD - Besut Daryanto; Athaya Febriantyo Purnomo; Taufiq Nur Budaya; Seskoati Prayitnaningsih; Nadia Artha Dewi (MNJ (Malang Neurology Journal), 2022)
Background: Nocturia is a common urinary system disease. Objective: This study aimed to investigate the causes of nocturia in women Indonesian inhabitants aged≥ 40 years. Methods: A stratified sample strategy was used to conduct a randomized cross-sectional study on 562 residents under the age of 40 in Malang City, East Java, Indonesia. A questionnaire was completed, which included socioeconomic demographics, lifestyle characteristics, and clinical history. Each night, nocturia was defined as at least two voids. The chi-squared test was used to determine proportional differences between age and gender groups. Multivariate logistic regression analysis was used to assess gender-related factors. This was determined that P0.05 was statistically significant. Results: Data on 562 people aged 61.60 + 9.81 years eligible for statistical analysis at the end, comprising 185 (32.92%) men and 377 (67.08%) women. Overall nocturia prevalence was 31.8% (179/562). It rose significantly with age (P<0.001) and reached >48% in those above the age of 70. In both men and women, nocturia was linked with diabetes, hypertension, cardiovascular disease, and the overactive bladder symptom score (OABSS) (P0.05). There was no link discovered between nocturia and education, profession, civil status, BMI, female birth history, or the International Prostate Symptom Score. Conclusion: Nocturia is linked to aging, cardiovascular disease, hypertension, OABSS, and diabetes in Indonesians over the age of 40.